Influence of Formulation and Rate on Rice Tolerance to Early-Season Applications of Acetochlor. (11th December 2018) - Fogleman, Michael; Norsworthy, Jason K.; Barber, Tom; Gbur, Edward
Abstract: Acetochlor (WSSA Group 15) is a very-long-chain fatty acid–inhibiting herbicide used to control grass weed species in row crops and could potentially be effective when used in a rice herbicide program. A field study was conducted in 2016 and 2017 at four locations to determine the effects of acetochlor formulation and rate on rice tolerance. Overall, rice was more tolerant to the microencapsulated (ME) formulation of acetochlor than to the emulsifiable concentrate (EC) formulation, likely because of the potential for immediate absorption of acetochlor from the EC formulation following rainfall. Differences in rainfall among experimental sites and years caused variation in acetochlor activation and influenced crop injury. In all environments, PRE applications of either formulation resulted in the greatest injury at 2 WAT (61%), while injury following delayed PRE (DPRE) or early POST (EPOST) applications averaged 30% and 16%, respectively. When ME acetochlor was applied EPOST, rough rice yield was 97% of nontreated rice or 9, 020 kg ha −1, indicating that applications should be delayed until this stage to minimize crop damage and maximize yield.